Lipid metabolism indicators provide tools for the diagnosis of non-alcoholic fatty liver disease: results of a nationwide survey - Wang, Yongxin; Fu, Chang; Jin, Hengwei; Yang, Yibo; Li, Xiaocong; Liu, Kai (Frontiers in Endocrinology, 2025)
BackgroundCardiometabolic index (CMI), visceral adiposity index (VAI), and lipid accumulation product (LAP) are lipid-related parameters that reflect central obesity, which is closely associated with the development of non-alcoholic fatty liver disease (NAFLD). The aim of this study is to investigate the effectiveness of these lipid-related parameters in diagnosing NAFLD and to compare their predictive abilities.MethodsThis population-based study extracted datasets from the National Health and Nutrition Examination Survey (NHANES) 2017–2020. CMI, VAI, and LAP were included in the multivariate logistic model as both continuous and categorical variables to assess the relationship between different lipid-related parameters and NAFLD. To further elucidate this connection, we utilized restricted cubic splines and conducted subgroup analysis. Additionally, the receiver operating characteristics (ROC) curve was employed to evaluate the predictive effectiveness of CMI, VAI, and LAP for NAFLD.ResultsThe study included 2,878 adults as the study population, of whom 1,263 participants were diagnosed with NAFLD. When lipid-related parameters were analyzed as continuous variables, they showed a positive correlation with NAFLD. The OR(95%CI) were 2.29(1.81,2.89) for CMI (per 1-unit), 1.40(1.28,1.52) for VAI (per 1-unit) and 1.15(1.11,1.20) for LAP (per 10-units). This correlation remains statistically significant when the lipid-related parameters are analyzed as categorical variables. In descending order of diagnostic capability for NAFLD, the AUC values are as follows: LAP (0.794), CMI (0.752), and VAI (0.719).ConclusionCMI, VAI, and LAP may be important clinical indicators for identifying NAFLD, with LAP demonstrating the best predictive ability among them.